Healthy migrant effect within Croatia - Kolčić, Ivana; Polašek, Ozren (2009)
Summary: The aim of this study was to investigate the demographic determinants and health status of within-country migrants in Croatia. Data from the Croatian Adult Health Survey from 2003 (N=9,070) were used in the analysis. Migrants due to 1991–1995 war were excluded from the analysis and only those who indicated that the reason for their migration within Croatia was related to employment or other reasons were included. Prevalence of hypertension and increased body weight was calculated for each of the three migration-related groups (employment-related migrants, other reasons migrants and non-migrants). Migrants were on general younger than non-migrants (more than three quarters of migrant were under 50 years). Employment-related migrants had the lowest prevalence of measured hypertension, while other reasons migrants had the lowest prevalence of increased body weight. Non-migrants had the worse indices in almost every trait and age group that was analysed. The results support the healthy migrant hypothesis, even in case of migrants who migrated within Croatia. However, the results of this study show that health status of migrants may depend on the reasons for their migration, suggesting that future migration studies should record and take this into account
Bibliografija: 16 jed
Keywords: Migracija -- Zdravstveno stanje; Hrvatska